Communication pour la santé : construction d’un champ de recherche et d’intervention - Lise Renaud (Communiquer)
In this article, a definition of the field of research and intervention on communication for health is proposed. This field involves the study and use of interpersonal, organizational and media communication strategies to inform and influence individual and collective decisions that improve health. Communication for health is a transversal and specific process. Then, the examination of the context of the development of communication for health at Université du Québec à Montréal (UQAM) is presented around two axes: the state of research in this field and the interests of UQAM, more particularly of the Département de communication sociale et publique. Finally, the evolution of the research conducted at the Centre de recherche sur la communication et la santé (ComSanté) with partners from the health and media sectors is described. In addition, the integrative model of the process of implementing a social standard through communications is offered.